UNMET NEED FOR FAMILY PLANNING ON ELIGIBLE COUPLE IN INDONESIA: 2007 IDHS DATA ANALYSIS - Nurul Fitriyah (UPT Penerbitan Universitas Jember)
In Indonesia, family planning program was succes .The successful achievement of ContraceptivePrevalence Rate (CPR) numbers can reduce theTotal Fertility Rate (TFR) of Indonesia. In 1971Indonesia TFR estimate of 5.6 (PSKK, 2004) andthen decreased to 2.4 (in 2002 ) , fell further to 2.3(in 2007) (Hull & Hartanto , 2009) . Unfortunately ,the percentage of the unmet need for familyplanning (unmet needs KB ) in Indonesia is still high. Based on data from Indonesian Demographic andHealth Survey (IDHS) unmet need for familyplanning Indonesia reached 13% ( 1991 ) , 11 % (1994 ) , 9.2 % ( 1997 ) and 8.6 % ( 2002 ) (PSKK,2004) . In 2007 unmet need for family planning by9.1 % ( BPS & Macro International , 2007), is stillfar from the target of Rencana PembangunanJangka Menengah Nasional ( RPJMN ) 2004-2009 ,which limits the number unmet need for familyplanning in Indonesia is not more than 6 % (President RI 2006 ) .Unmet need for family planning has a direct impacton a country's TFR . If unmet need family planningcan be eliminated , there will be a sharp decline inbirth rate, along only consider contraception factoralone ( Mueller & Germain , 2007). Based onRPJMN 2004-2009, target of TFR Indonesia expectsno more than 2.2 ( Presiden RI , 2006) . Therefore ,the handling of unmet need for family planning arestrong reasons for the planning andimplementation of effective family planningprogram ( Bongaarts & Bruce , 1995; Sedgh et al. ,2007) .Ashford (2003) describes when in the developingworld, more than 100 million women, or 17% of allwomen married status unmet need for familyplanning. Because of the magnitude of unmet needfamily planning, so it is important to handlingunmet need for family planning immediately.Unmet need for family planning caused unexectedpregnancy (unintended pregnancy) (Haub &Herstad, 2002), which can lead to unsafe abortions(unsafe abortion) (Bizuneh et al., 2008). Unsafeabortion is responsible for 11% of maternal deathsin Indonesia and the world average of 13%(Wilopo, 2009). Seeing the magnitude of theunmet need for family planning, it is necessary toresearch related to the incidence of unmet needfor family planning on eligible couples in Indonesia.